The spectrum of clinical presentation in haploinsufficiency of A20; a case report of a novel mutation in TNFAIP3 gene - Debeljak, M.; Blazina, S.; Brecelj, J.; Avčin, T.; Toplak, N. (Frontiers in Pediatrics, 2023)
Haploinsufficiency of A20 was first described in 2016 as a new autoinflammatory disease that clinically presents as early-onset Behcet's disease. After the publication of the first 16 cases, more patients were diagnosed and described in the literature. The spectrum of clinical presentation has expanded. In this short report, we present a patient with a novel mutation in the TNFAIP3 gene. The clinical presentation included signs of an autoinflammatory disease with recurrent fever, abdominal pain, diarrhea, respiratory tract infections, and elevated inflammatory parameters. We will emphasize the importance of genetic testing, especially in patients with various clinical signs that do not fit a single autoinflammatory disease.